PROFIL KEMAMPUAN BERPIKIR ANALISIS DAN EVALUASI MAHASISWADALAM MENGERJAKAN SOAL KONSEP KALOR - Winarti . (Universitas Sriwijaya, 2015)
Analytical skills and the ability to evaluate the capabilities required to master students in solving problems in physics . Analysis and evaluation is also important to have in the material of heat because some of the concepts of heat that occurs in everyday life is not in accordance with the theory . This research is a descriptive study that aims to determine the level of analytical skills and ability to evaluate students in working on the concept of heat . The instrument used in this study of the test material type description kalor.Berdasarkan data analysis can be described that level analytical skills of students on three indicators of differentiating has a value of 16.6 , 46.6 and attributing organizing of 7.2 . In the analytical skills of students is at a low level . To evaluate the ability of obtained scores of 86.6 for checking and critiquing the score for the indicator value is at a low level of 23.3 .